2024
DOI: 10.3390/su16020829
|View full text |Cite
|
Sign up to set email alerts
|

The University and the Neighbourhood—Opportunities and Limits in Promoting Social Innovation: The Case of AuroraLAB in Turin (Italy)

Francesca Bragaglia

Abstract: This paper deals with the relationship between university public engagement activities and local territories in promoting social innovation processes. In particular, this paper starts from the assumption that since social innovation has become a guiding concept of policies at various scales, opportunities for innovation, i.e., calls for tenders, funding, etc., have multiplied. However, universities should act as intermediary actors so that the bureaucratic and managerial complexities of accessing these opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Moreover, the research has shown that former public buildings, as pointed out in Section 2, can become commons [59] able to generate new social or cultural economies [46], with a strong orientation towards answering the collective needs of increasingly vulnerable or fragmented communities. Therefore, serving the double purpose of animating and/or revitalizing deprived or distressed urban neighborhoods and of shaping new values, where social and cultural objectives become as important as economic ones, these are interpreted as a distinctive feature of the interactive growth process that local administrations are increasingly experiencing [60,61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the research has shown that former public buildings, as pointed out in Section 2, can become commons [59] able to generate new social or cultural economies [46], with a strong orientation towards answering the collective needs of increasingly vulnerable or fragmented communities. Therefore, serving the double purpose of animating and/or revitalizing deprived or distressed urban neighborhoods and of shaping new values, where social and cultural objectives become as important as economic ones, these are interpreted as a distinctive feature of the interactive growth process that local administrations are increasingly experiencing [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of territorial entrepreneurs in the networks shaping the projects can be considered a relevant condition of culture-based regeneration projects, we agree with Tricarico et al [63] that a territorial entrepreneur can act successfully only if he/she is able to build effective alliances among actors and activate what several scholars define as «platform spaces», namely «cultural and creative places where social innovation plays a key role in community engagement activities as well as generating horizontal/collaborative interactions among different stakeholders and their interests while aligning with territorial development targets» [63] (p. 2). The emphasis of these platform spaces is often oriented towards providing multi-actor and bottom-linked action arenas where different actors and networks collaborate, (co)produce, and exchange knowledge via collective and creative learning [15,61,64]. In other terms, the purpose of these arenas is to shape collaborative spaces where the collective initiatives of citizens and innovators can flourish, building agreements and collaboration with local administrations that can enable such initiatives through sound, regulated, and lasting practices [18].…”
Section: Discussionmentioning
confidence: 99%